Validation of Enzyme Immunoassay for Preclinical Pharmacokinetic Trials of Rituximab - V. V Pisarev; Maria M Ulyashova; Gelia N Gildeeva (Регуляторные исследования и экспертиза лекарственных средств)
An integral part of preclinical pharmacokinetic studies is the development of a bioanalytical method for determination of the drug in a biological fluid.The aim of the research was to assess the suitability of the test system based on enzyme-linked immunosorbent assay (ELISA) for quantitative determination of rituximab in the blood serum of laboratory animals after intravenous administration of rituximab at a dose corresponding to the therapeutic dose in humans. Th test system was developed by the Scientific and Production Center Probiotech.Materials and methods: the determination of rituximab in biological samples was carried out using a two-stage sandwich-type ELISA, followed by detection based on horseradish peroxidase. The ELISA results were recorded using a microplate photometer at a wavelength of 450 nm.Results: the experiments helped to establish the detection limit (0.24 ng/mL) and the lower limit of quantitation (1.00 ng/mL) of rituximab in rabbit blood serum, they also demonstrated high selectivity of analyte determination in a multicomponent biological matrix. The mean rituximab concentration was within 14 % of the nominal value in the entire working range of the method. The within-run and between-run precision of the assay did not exceed 7.4 %, the total error of the method did not exceed 20.1 %. The linearity of dilution makes it possible to use the assay for the analysis of biological samples with a wide range of rituximab concentrations. The stability of the analyte in the rabbit blood serum was confirmed by storing samples for 6 hours at room temperature, for 50 days at —35 °C, and after 3 freeze-thaw cycles. The validated immunoassay was successfully used to determine the rituximab concentration in biological samples obtained in the rituximab pharmacokinetic trial in rabbits. The accuracy of the results was confirmed for the entire range of the determined concentrations; parallelism was demonstrated between the calibration curve and the results of analysis of serially diluted rabbit serum samples with the maximum concentration of rituximab.Conclusions: the proposed enzyme immunoassay test system can be used for quantitative determination of rituximab in the blood serum of laboratory animals, as it meets acceptance criteria for all validation parameters described in the international guidelines on validation of bioanalytical methods.